Spinal melanoma with optic neuropathy –rare manifestation of Neurocutaneous melanosis and PET-MRI findings - Dipti Baskar; Seena Vengalil; Priyanka Chakkera; Sai Bhargava Sanka; Pritam Raja; Karthik Kulanthaivelu; Preetham Patavardhan; Keerti Sitani; Yasha T. Chickabasaviah; Nupur Pruthi; Atchayaram Nalini (eNeurologicalSci)
Neurocutaneous melanocytosis (NCM) is a rare, sporadic neuroectodermal dysplasia characterized by the presence of large or multiple congenital cutaneous nevi and melanocytic deposits in the central nervous system. Hitherto, unreported we describe a case of NCM with optic neuropathy and spinal cord melanoma from India. A 20 year-old-lady had headache and vomiting for 3 months followed by consecutive profound painless visual impairment. Visual acuity was counting of fingers at 1 m distance in both eyes with normal fundus. There were no symptoms of spinal cord involvement. Clinical examination showed multiple small to large melanocytic nevi over the face and body. Muscle power was normal. Tendon reflexes were exaggerated. Visual evoked potential showed bilateral prolonged P100 latency (Right eye - 144 msec; Left eye - 151 msec). Brain MRI revealed leptomeningeal enhancement of brainstem, cerebellum, oculomotor and facial-abducent nerve complex without optic nerve involvement. MRI spine showed extensive dorsal thoracic cord epidural lesion extending along the entire thoracic cord segment with dorsal cord compression. Positron Emission Tomography (PET) imaging showed Fludeoxyglucose F18 (FDG) avidity along D1-D12 levels of spinal cord. Biopsy from the cord lesion was suggestive of meningeal melanoma. Here we document a rare case of late onset NCM with intracranial meningeal infiltration and asymptomatic large epidural lesion of spinal cord, expanding its phenotypic spectrum. Optic neuropathy in NCM has not been reported earlier. Periodic screening of brain and spine is recommended for early prognostication and lesion identification in NCM.